Analisis Kualitatif pada Komunitas Gamers Surabaya dalam Memutuskan Pembelian Headset Gaming Merek Fantech - Sari, Dia Mega Indah; Sugeng Purwanto, (Jurnal Manajemen, 2023)
In this increasingly modern era, the increasing popularity of electronic esports, commonly known as E-sports, has become a magnet for some people to try playing games. Accessories or additional game equipment, including keyboards, mice, headsets, and mousepads, are often called gaming gear. Fantech is a product developed by a peripheral gaming company from Indonesia founded in 2009 by three brothers. Researchers are interested in examining how a Fantech Gaming Headset Brand Image as a Brand or Gaming Headset Brand. Using qualitative analysis, it was found that product trust, benefits, service, and price are the hallmarks of the Fantech gaming headset product. Risk factors have the lowest average score, which explains that Fantech gaming headset products have a high risk of product damage, which can make high warranty claims.